Study of Hibiscus Rosasinensis as a Feedstock for Natural Colorant to Food (Chemical Engineering Research Bulletin, 2021)
The application of coloring to food is widespread around the globe. Some of the artificial food colorants are highly carcinogenic. Exploration of new natural colorants has therefore been under research. The present study was aimed to evaluate Hibiscus rosasinensis flower as a potential feedstock for natural colorant. Crude anthocyanin was first extracted from Hibiscus rosasinensis flower using a Soxhlet apparatus with ethanol as the solvent. Flower to solvent ratio was found to affect the extraction largely. A ratio of 1:20 was found to give the highest fraction of extract. The cytotoxicity of crude anthocyanin extract was subsequently determined by Brine Shrimp Lethality Test. The LC50 value for crude anthocyanin extract was 2332 μg/ml, which is higher than the required minimum threshold value. Hence the findings of present study would be useful towards the application of H. rosasinensis flower as a feedstock for natural colorant to food.Chemical Engineering Research Bulletin 21(2020) 32-36